MICROLEARNING VIDEOS THROUGH TECHNOLOGICAL, PEDAGOGICAL, AND CONTENT KNOWLEDGE: THE LENS OF USER EXPERIENCE - Aladawiya, Rabia; Suparno; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This research aims to explore and understand user experiences in the context of developing technology, pedagogy, and content knowledge-based microlearning videos. Qualitative research methods were employed to gain in-depth insights into how educators and learners utilize and interpret the implementation of Basic Marketing Principles through microlearning videos. The study focused on students in the 10th grade specializing in Marketing at State Vocational High School 12 Jakarta. The research approach involved data collection through in-depth interviews and participatory observations of the use of microlearning videos. The findings indicated that the developed microlearning videos received positive validation from media and content experts. Evaluations from both teachers and students revealed a high level of acceptance of microlearning videos during the learning process. Consequently, this research provides a meaningful learning experience by presenting short, focused learning media that can be easily accessed at various times and locations.